AGN Service and Driving Range Operation Management System - Goh Sian Hang; Muhammad Samsu Sajat (Multidisciplinary Applied Research and Innovation, 2021)
AGN (Akademi Golf Nasional) Services and Driving Range Operation Management System is a web-based system that developed to provide a platform to fulfil the needs from different type of users who involved in golf industries or activities. The existing system of AGN service are lacking its own registration and management features for admin and users to manage general affairs related to golf activities. The objective is to develop the system is to identify requirement, design, develop and test the system in terms of functionalities. To achieve project, throw-away prototyping development methodology was applied to develop a web-based system to complete and achieve client requirements. The expected result of project is to ensure the web-based system can be completed with minimalistic interface designs with responsive functionalities.